A child's look at the Twenty-third Psalm - Keller, W. Phillip (Weldon Phillip), 1920-1997 (Doubleday, 1981)
Explores the meaning of the 23d psalm in which Christ's love for his followers is likened to that of a shepherd's for his flock.